2003
DOI: 10.1111/j.1728-4457.2003.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Explaining Fertility Patterns: Preference Theory

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Population Council is collaborating with JSTOR to digitize, preserve and extend access to Population and Development Review. have attracted substantial research attention and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
265
0
24

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(307 citation statements)
references
References 34 publications
8
265
0
24
Order By: Relevance
“…Our findings show an opposite pattern for men; those with children have stronger economic positions than those who have remained childless. In our society, the gender-based division of tasks leads to greater restrictions on combining work and childcare responsibilities for women than men (Wetzels, 2001;Hakim, 2003;Kemkes-Grottenthaler, 2003;Schippers, 2003). Women, rather than men, encounter the opportunity costs of having children.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show an opposite pattern for men; those with children have stronger economic positions than those who have remained childless. In our society, the gender-based division of tasks leads to greater restrictions on combining work and childcare responsibilities for women than men (Wetzels, 2001;Hakim, 2003;Kemkes-Grottenthaler, 2003;Schippers, 2003). Women, rather than men, encounter the opportunity costs of having children.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gender sets the context of lives, reflecting not only physiological differences, but also unique structural circumstances. For example, in society, the gender-based division of tasks leads to greater restrictions on combining work and childcare responsibilities for women than men (Wetzels, 2001;Hakim, 2003;Kemkes-Grottenthaler, 2003;Schippers, 2003). Previous studies have rarely considered the gendered life course processes though which people remain childless: women are the primary focus in childlessness research, and men have been largely neglected (Greene & Biddlecom, 2000;Forste, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…They also more readily http://dx.doi.org/10.15405/epsbs.2017.01.02.4 Corresponding Author: Anna Bagirova Selection and peer-review under The identified differences could also be explained in terms of Catherine Hakim's Preference Theory (Hakim 2003), according to which women's lifestyle preferences are a key fertility factor. Our results correspond to the lifestyle preferences she identified: career-oriented, family oriented, oriented towards combining work and family.…”
Section: Resultsmentioning
confidence: 99%